Validation of the name Oenothera hoelscheri var. albinervis (Onagraceae) - Woźniak-Chodacka, Monika (Phytotaxa, 2016)
Oenothera hoelscheri Renner (1942: 460) ex Rostański (1968: 189) is one of about 100 taxa of the genus Oenothera (section Oenothera subsection Oenothera) observed in the European continent (based on research made by Hudziok (1968), Soldano (1992), Rostański (in: Rostański et al. 2010) and others). It originated as a result of hybridization: O. rubricaulis Klebahn (1914: 12) × O. hungarica (Borbás 1902: 204) Borbás (1903: 246) = O. depressa Greene (1891: 216) (Renner 1942). The first specimen of O. hoelscheri was collected in Włocławek (Poland: kujawsko-pomorskie) by R. Hölscher (Renner 1942). Currently, the taxon is relatively wide distributed in Central, East and North Europe (Rostański et al. 2010).